AUTOLOGOUS NEUROSENSORY RETINAL TRANSPLANTATION: Bridging the Gap. Issue 12 (December 2021) - Patel, Saagar N.; Mahmoud, Tamer H.; Kazahaya, Masayuki; Todorich, Bozho
Abstract : Purpose: To review the autologous retinal transplantation surgical technique, indications, rationale, and current outcomes of data published to date. Methods: Review of surgical technique, preoperative and postoperative best-corrected visual acuity, and macular hole (MH) closure rate in studies with at least five eyes. Results: The weighted average macular hole closure rate is 88%, with a MH closure rate ranging from 66.7% to 100%. The weighted average best-corrected visual acuity improved from mean logarithm of the minimum angle of resolution 1.35 (Snellen equivalent of 20/450) preoperatively to mean logarithm of the minimum angle of resolution 1.02 (Snellen equivalent of 20/210) postoperatively. From the largest autologous retinal transplantation case series, 37% of patients gained 3 or more lines of visual acuity after autologous retinal transplantation for primary or refractory MHs and 74% gained 3 or more lines of visual acuity after autologous retinal transplantation for MH–retinal detachments. Functional improvement including negative Watzke–Allen sign and conversion from positive to negative scotoma was reported in large case series. Conclusion: Autologous retinal transplantation is a promising technique for closure of large and refractory MHs otherwise difficult to repair with conventional techniques. This technique may allow for replacement of neural tissue in the macula through cell rehabilitation and regeneration through presumed ectopic synaptogenesis, retinal progenitor cell differentiation and integration, and/or retinal progenitor cell material transfer to host neurons. Abstract : Autologous retinal transplantation for large primary or recurrent macular hole and large macular hole-associated retinal detachments is an emerging technique for macular holes that did not or otherwise would not close with traditional surgical approaches. We review the surgical technique, indications, rationale, and current data on outcomes with this novel technique.